The Influence of Financial Literacy, Risk Management, Trading Psychology, And Use Analysis Technical to Trading Decisions for Beginner Traders - Moch Ramadhani Firmansyah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of financial literacy, risk management, trading psychology, and the use of technical analysis on trading decisions among novice traders in Lamongan Regency. This research employs a quantitative approach using a structured questionnaire survey method. The research population consists of all active novice traders in stock, forex, and cryptocurrency markets in Lamongan Regency. Purposive sampling was employed to obtain 100 respondents. Data analysis was conducted using multiple linear regression with SPSS 26 software. The results indicate that financial literacy (β = 0.287; p < 0.05), risk management (β = 0.312; p < 0.05), trading psychology (β = 0.198; p < 0.05), and technical analysis usage (β = 0.241; p < 0.05) each have a partial positive and significant effect on trading decisions. Simultaneously, all four variables significantly influence trading decisions with F = 28.74 (p < 0.05) and a coefficient of determination (R²) of 0.542, indicating that 54.2% of the variation in trading decisions is explained by the four independent variables. The findings emphasize the importance of enhancing financial literacy, implementing disciplined risk management strategies, managing psychological aspects, and appropriately utilizing technical analysis to support better trading decision-making.